Enhancement of RNA polymerase II initiation complexes by a novel DNA control domain downstream from the cap site of the cytomegalovirus major immediate-early promoter. - Ghazal, P (1991)
The major immediate-early promoter (MIEP) of human cytomegalovirus is a remarkably strong RNA polymerase II transcription control unit. We have identified and characterized a novel regulatory domain associated with MIEP downstream from the initiation site of transcription. The downstream regulatory region was first identified by analyzing a series of mutations in the 5' untranslated leader exon. This regulatory domain was shown to enhance the number of functional initiation complexes without significantly altering the apparent elongation rate by RNA polymerase II transcription. In addition, run-off in vitro transcription and DNA-binding experiments identified two distinct downstream elements that specify the interaction of cellular transcription factors. One of these elements contains a reiterated sequence motif, present twice within the leader exon. The second element is an 18-bp sequence located at approximately nucleotide position +33 that is conserved between strains of cytomegalovirus from different species. On the basis of two criteria, an oligonucleotide competition assay and oligomerization upstream of the promoter, the binding of factors to the conserved box was shown to be critical for mediating the level of transcription from MIEP. Two discrete cellular nuclear proteins, designated LTF A and B (for leader transcription factor A and B binding factors), were found to specifically recognize the conserved element. This study of promoter-proximal elements within transcribed sequences demonstrates the recognition of the control domain at the DNA level that functions to increase the number of committed RNA polymerase II transcription complexes.